A formação politica no material de sociologia e projeto de vida do ensino médio da rede estadual paulista - Chiló, Marcelo Cardoso (2023)
This qualitative investigation and documentary research methodology aims to understand the proposal for political formation present in the didactic material "Curriculum in Action" (2022) in the area of Human and Social Sciences of High School in the state of São Paulo, in the disciplines of Sociology and Life Project. To do so, we debate the context of high school and political education in youth. In order to understand what constitutes this formation, it was necessary to carry out a bibliographic survey that would subsidize the elaboration of a typology for political formation. Contextualized in the debate on youth and politics, discussions on “Education for Democracy” were mapped; “Aspects of Political Socialization in Youth”; and “Education as a Political Act”, based on which a typology was proposed for political formation containing: “Civic Formation”, “Democratic Formation”, “Self-promoted Formation”, “Emancipatory Formation” and “Self-made Formation”. Based on the data analyzed, it was observed that the “Curriculum in Action” tends to develop up to three types of political training: in Sociology, priority is given to Political Training of the Civic type, reinforcing the expository and content-oriented form of information about politics; there are times when the material tries to approach Democratic Political Formation, however, this depends on countless other factors that go beyond the didactic material for its effective practice; in Life Project, there is a strong presence of Self-made Political Formation, proving to be an instrument for evaluating young people's conduct and behavior linked to the conception of education conceived by business reformers. Finally, the emptying of disciplines in the humanities is concluded, since the option for the creation of a new curricular component to address themes close to the area is justified by an approach exempt from the critical look already offered by the Humanities and Social Sciences.